2011
DOI: 10.5301/hip.2011.8845
|View full text |Cite
|
Sign up to set email alerts
|

Fluid Extravasation during Hip Arthroscopy

Abstract: The amount of fluid that may be lost into the soft tissues during hip arthroscopic surgery is unknown. We measured the volumes of irrigation fluid infused, operating time, fluid pressures and volumes of fluid recovered in 36 therapeutic hip arthroscopies. We excluded those where fluid was lost to the floor, leaving 28 patients. The majority were undergoing surgery for the treatment of femoroacetabular impingement. In 5 patients an intra-articular contrast medium was instilled, in order to establish the likely … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
19
1
1

Year Published

2012
2012
2019
2019

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(22 citation statements)
references
References 10 publications
1
19
1
1
Order By: Relevance
“…Aside from iliopsoas release, the length of the operation and the volume of fluid infused during the procedure are significant predictors of fluid extravasation. 43 Strategies for preventing large-volume fluid extravasation include avoiding hip arthroscopy in the setting of acetabular fracture; decreasing pump pressures; frequent palpation of the abdomen by the surgeon; good communication with the anesthesia team regarding the potential of fluid extravasation and the potential for unexplained hypotension or hypothermia; and, if an iliopsoas release is indicated, performing the procedure at the end of the surgical case.…”
Section: Abdominal/thorax Fluid Extravasationmentioning
confidence: 99%
“…Aside from iliopsoas release, the length of the operation and the volume of fluid infused during the procedure are significant predictors of fluid extravasation. 43 Strategies for preventing large-volume fluid extravasation include avoiding hip arthroscopy in the setting of acetabular fracture; decreasing pump pressures; frequent palpation of the abdomen by the surgeon; good communication with the anesthesia team regarding the potential of fluid extravasation and the potential for unexplained hypotension or hypothermia; and, if an iliopsoas release is indicated, performing the procedure at the end of the surgical case.…”
Section: Abdominal/thorax Fluid Extravasationmentioning
confidence: 99%
“…Early literature on hip arthroscopy suggested that some fluid inevitably escapes into the abdomen to be subsequently resorbed. 7 Stafford, Malviya and Villar 49 recently reported a mean extravasation of 1132 ml (95% confidence interval (CI) 808 to 1456) of irrigation fluid into peri-articular tissues. The surgeon should always be aware of the ingress–egress balance of irrigation fluid during the procedure.…”
Section: Fluid Extravasationmentioning
confidence: 99%
“…Stafford et al 7 reviewed 36 patients undergoing hip arthroscopy performed by one physician in one facility. Researchers measured the volume of irrigation fluid infused, operating time, fluid pressures, and volumes of fluid recovered during all 36 procedures.…”
Section: Measuring Fluids During Minimally Invasive Surgery Proceduresmentioning
confidence: 99%
“…There was a correlation between the volume of extravasated fluid and both the length of surgery and the volume of infused fluid used. The authors concluded that reduced operative times (ie, <90 minutes) and fluid pressure at low rates (ie, <50 mm Hg) reduced the risk of fluid extravasation 7 …”
Section: Measuring Fluids During Minimally Invasive Surgery Proceduresmentioning
confidence: 99%